Adefovir dipivoxil-associated Fanconi syndrome combined with peripheral neuropathy: a case report and literature review - Fu, Shanshan; Wu, Guanao; Zhao, Yuanqi; Zhao, Min (Frontiers in Pharmacology, 2025)
Long-term use of low-dose adefovir dipivoxil (ADV) has been increasingly associated with Fanconi syndrome; however, cases of Fanconi syndrome combined with peripheral neuropathy remain rare. Here, we report a 67-year-old man who developed progressive limb weakness and sensory abnormalities after approximately 6 years of treatment with 10 mg ADV. He was diagnosed with ADV-associated Fanconi syndrome accompanied by peripheral neuropathy. Following the substitution of ADV with entecavir and 5 months to 6 months of phosphate supplementation, the patient’s muscle weakness nearly resolved, and peripheral nerve damage showed significant improvement.